2016
DOI: 10.1016/j.amjsurg.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Where do we start? The first survey of surgical residency education in Japan

Abstract: Background: Currently, Japan does not have a national standardized program for surgical residency. Therefore, surgical education information and strategies are not shared among teaching hospitals. This was the first study aiming to clarify the current situation of surgical residency in Japan. Methods:A questionnaire survey investigating the present situation of surgical residency was sent to the 76 teaching hospitals in Hokkaido Prefecture, Japan. Results:The response rate was 64.5%. Data from the 36 hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In our survey, 45% of institutes had their own assessment tool within the surgical department. This percentage is slightly lower than that from a survey conducted in Japan in 2016, where 55% of surgical training institutes had their tool for assessing the capabilities of residents [12]. However, only 31% of training institutes stored its assessment forms.…”
Section: Discussionmentioning
confidence: 75%
“…In our survey, 45% of institutes had their own assessment tool within the surgical department. This percentage is slightly lower than that from a survey conducted in Japan in 2016, where 55% of surgical training institutes had their tool for assessing the capabilities of residents [12]. However, only 31% of training institutes stored its assessment forms.…”
Section: Discussionmentioning
confidence: 75%
“…[15] [ 33] Despite the potential of surgical simulators, they are not in regular use for residential training, a study in Japan showed that only 12.5% of the university hospitals integrate surgical simulators in their surgical training regularly; however, a survey made in 2013 shows that 77% of surgical residency programs in the US use surgical simulators during their program. [34] Pre-operative planning in the field of orthopaedic is another use for surgical simulators. A study on their utility for surgical planning shows that they can offer a reduction in operation time of 19.85% and a diminution of intra-operative blood loss of 25.73%.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, most of the surgical training has been conducted as "on the job training" without structured curriculum for a long while, and more priority has been given to clinical work and research compared with resident education in teaching hospitals. While recently, there is a tendency for the university-based teaching hospitals to have more resources and teaching staff available for resident education, most community hospitals cannot afford to employ dedicated teaching staff for resident education [5]. This situation can also be seen in other countries.…”
Section: Current Hpb Surgical Training Modelmentioning
confidence: 90%